A clinical study on multi-drug resistant Streptococcus pneumoniae respiratory infections in adult patients - Tamada, Sadao; Matsushima, Toshiharu; Nakajima, Masamitsu; Fujii, Chiho; Niki, Yoshihito (Japanese Journal of Chemotherapy, 1996)
A clinical study on multi-drug resistant Streptococcus pneumoniae respiratory infectons in adult patients was performed. One hundred twenty strains of S. pneumoniae were isolated from different patients at the clinical microbiology laboratory of Kawasaki Medical School Hospital between November 1993 and February 1995. All of these patients' clinical records were reviewed to determine the backgrounds of patients such as age, diagnosis of infections, underlying disease, division where the patients were treated etc. Then, 78 adult patients with pneumococcal respiratory infections were selected as the study subjects. There were 32 patients with pneumonia, 18 with chronic respiratory tract infections and 28 with other respiratory infections. Fifty patients were treated in the division of internal medicine and 24 were treated in the emergency unit. The overall rate of resistant S. pneumoniae in these patients, was 46.7%; intermediately resistant (PISP) 25.8% and resistant (PRSP) 20.9%. In pneumonic cases, the resistant rate was only 15.4% in patients in the internal medicine division while a high resistant rate of 72.7% was observed in patients treated in the emergency unit, most of whom had severe underlying diseases and were treated by antibiotics selected by a different policy. The resistance rates were also higher in aged patients with pneumonia. A high resistance rate was also noted in patients with chronic respiratory tract infections who had many more opportunities to have frequent chemotherapy. The clinical effectiveness of penicillins and 1st generation injectable cephalosporins in the treatment of these resistant pneumococcal infections was not always satisfactory. However, in some patients with PISP pneumonia, high-dose penicillin G treatment was highly effective.These results suggest that consideration of the patient's condition and characteristics of drugs are important in the treatment of these resistant pneumococcal infections.